Dengue Virus-Induced Inflammation of the Endothelium and the Potential Roles of Sphingosine Kinase-1 and MicroRNAs. (2nd November 2015) - Aloia, Amanda L.; Abraham, Alexander M.; Bonder, Claudine S.; Pitson, Stuart M.; Carr, Jillian M.
Abstract : One of the main pathogenic effects of severe dengue virus (DENV) infection is a vascular leak syndrome. There are no available antivirals or specific DENV treatments and without hospital support severe DENV infection can be life-threatening. The cause of the vascular leakage is permeability changes in the endothelial cells lining the vasculature that are brought about by elevated vasoactive cytokine and chemokines induced following DENV infection. The source of these altered cytokine and chemokines is traditionally believed to be from DENV-infected cells such as monocyte/macrophages and dendritic cells. Herein we discuss the evidence for the endothelium as an additional contributor to inflammatory and innate responses during DENV infection which may affect endothelial cell function, in particular the ability to maintain vascular integrity. Furthermore, we hypothesise roles for two factors, sphingosine kinase-1 and microRNAs (miRNAs), with a focus on several candidate miRNAs, which are known to control normal vascular function and inflammatory responses. Both of these factors may be potential therapeutic targets to regulate inflammation of the endothelium during DENV infection.